Development level of electronic government services: An empirical study of e-government websites in Pakistan. Issue 1 (6th December 2018) - Butt, Nadia; Warraich, Nosheen Fatima; Tahira, Muzammil
Abstract : Purpose: This paper aims to explore the emerging trends of e-government in Pakistan with an empirical investigation of the e-government websites and the services they provide to the citizens of Pakistan. It also investigates the level of development of these e-government websites in the Punjab Web portal. The governments in Asian countries, including Pakistan, have been struggling to switch their services from traditional on-spot services to online services. Focal points of the study are development level of e-government websites, available e-services and quality. Design/methodology/approach: The e-government Web portal of Punjab province with 38 websites is center of attention in present study. Website's content analysis method is used to study e-government websites ( N = 38) from the Punjab Web portal. It used the "Four-Stage Development Model" for the four stages, namely, "publishing", "interacting", "transacting" and "transforming", to study the phenomena. Findings: The findings showed that most of the websites on the Web portal were at the first (publishing) and second (interacting) stage of development. For the provision of effective online services, websites need to be on the third (transacting) and fourth (transforming) stage. Only a few websites in the Punjab Web portal were the on transacting and transforming stages providing a mature level of services. In total, 40 different types of services are identified in 38 websites of Punjab e-government Web portal. Practical implications: E-government, Web portals are developed to give citizens a single, easy access point to several departments' websites and their services. This baseline study recommends to update e-government websites periodically and put more focus on technological and contextual features to enhance the accessibility and usability of the websites. Originality/value: This is first empirical study of e-government websites to explore their services and examine existing level of website development in this region.